Encapsulation of Lactobacillus plantarum ISO14 for synbiotic tilapia feed formulation - Jahari, Muhamad Amin (2019)
The increase cost of producing tilapia coupled with vigorous expansion of the industry pose a serious problem to the performance of the fish that lead to farmers loss. There is a need to develop feed additives incorporated in feed formulations to improve fish growth. The purpose of this study is to formulate a fish feed with synbiotic through encapsulation of Lactobacillus plantarum ISO14 with mannan to improve tilapia growth performance. The mannan was derived from palm kernel cake (PKC) and has the property of prebiotic. Since PKC are abundant and sustainable in Malaysia, its price is relatively low compared to imported ingredients and its supply for continuous fish feed production is promising. Encapsulation matrices optimization by response surface methodology (RSM) showed 1.66 % (w/v) of sodium alginate and 24.73 % (w/v) of mannan as coating materials would produce the highest survival of the probiotic. The verification experiment yielded a result close to the expected values, with no significant difference (P > 0.05) suggesting the model is adequate to be used as predictive model. The feed were formulated according to National Research Council (NRC) of standard tilapia nutritional requirement and added with encapsulated bacteria. Feeding trials in laboratory scale and industrial scale were conducted on growth performance of the tilapia. The fish were randomly assigned to two dietary treatments; control diet (without synbiotics) and synbiotic diet. Laboratory scale feeding demonstrated that synbiotic fed fish had a better growth rate with 12.6 ± 0.11 g fish-1 of weight gain compared to control fed fish 9.7 ± 0.04 g fish-1. Feed conversion ratio (FCR) was also significantly lower in the synbiotic fed fish, 1.53 gg-1, compared to the control fed fish1.85 gg-1 suggesting a higher growth performance in synbiotic fed fish. Similar results were observed in the industrial scale feeding with synbiotic fed fish showed a better feed efficiency (P < 0.05) with the FCR of 2.12 gg-1 compared to control fed fish 2.30 gg-1. This study has contributes to a development of fish feed supplemented with synbiotics that able to increase tilapia growth performance in a sustainable way.